An Overview for Living in Extraterrestrial Universe without DNA & RNA: Higgs Boson or God Particle as a Common Origin for Universal Life and Living Essence Existence - (:unkn) unknown (AMG Transcend Association, 2022)
Obviously, the initial biopolymer for any type of universal life on another planet must satisfy other construction of life. Therefore, synthetic enzymes hinted related to cosmic life without DNA or RNA might be produced in another part of the universe. Enzymes can be made from quasi genetic material that does not exist on Earth. So, this discussion is a fundamental theory for the possibility of life that could evolve without DNA or RNA (whom these two self-replicating units for life on Earth). Our universe is surprising in many aspects, allowing for everything we see to exist. Therefore our universe might be the exception that is balanced in this way, and it is only in this balance can there be life. Interestingly, 3 quarks could still exist without the Higgs field, but the electron would remain massless, which means there would no longer be atoms of any kind, no biomolecules, DNA, RNA, and no life.